Alpha modulation via transcranial alternating current stimulation in adults with attention-deficit hyperactivity disorder - Kannen, Kyra; Rasbach, Johanna; Fantazi, Amin; Wiebe, Annika; Selaskowski, Benjamin; Asché, Laura; Aslan, Behrem; Lux, Silke; Herrmann, Christoph S.; Philipsen, Alexandra; Braun, Niclas (Frontiers in Psychology, 2024)
Background: One possible therapy treating attention-deficit/hyperactivity disorder (ADHD) is to modulate dysfunctional brain activations using brain stimulation techniques. While the number of studies investigating the effect of transcranial direct current stimulation on ADHD symptoms continues to increase, transcranial alternating current stimulation (tACS) is poorly examined. Previous studies reported impaired alpha brain oscillation (8-12 Hz) that may be associated with increased attention deficits in ADHD. Our aim was to enhance alpha power in adult ADHD patients via tACS, using different methods to explore potential therapeutic effects.Methods: Undergoing a crossover design, adults with ADHD received active and sham stimulation on distinct days. Before and after each intervention, mean alpha power, attention performance, subjective symptom ratings, as well as head and gaze movement were examined.Results: Frequency analyses revealed a significant power increase in the alpha band after both interventions. Despite a trend toward an interaction effect, this alpha power increase was, however, not statistically significantly higher after active stimulation compared to sham stimulation. Some additional pre-post effects were found for the other measures, which were not intervention-related.Our study cannot provide clear evidence for a tACS-induced increase in alpha power in adult ADHD patients, and thus no stimulation related improvement of attention parameters. We provided further recommendations for the future investigation of tACS as a potential ADHD treatment. hat gelöscht: , 32 hat gelöscht: except for an increase in subjective impul-33 sivity under sham but not under tACS.